Determinan Belanja Modal pada Provinsi di Sumatera dan Jawa - Afifah Putri Salamah; Maria Maria; Rosy Armaini (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine the influence of General Allocation Funds, Original Regional Income, Receiving costs, and Remaining Budget Financing on ModaI Expenditures in the provinces of Sumatera and Java partially and simultaneously. This research uses a quantitative approach covering all 16 provinces in Sumatra and Java from 2018-2022. Data obtained from audited LKPD obtained from the BPK RI website. The results of this research show that ORI partially influences capital expenditure. Meanwhile, GAF, financing revenues and Remaining Budget Financing do not partially influence capital expenditure. GAF, ORI, financing revenues and Remaining Budget Financing simultaneously influence capital expenditure. These findings contribute to regional governments paying more attention to the factors that influence capital expenditure in their respective regions. The existence of data that does not meet the criteria means that the research cannot describe the population as a whole.